Simulation-based assessment methodology to improve ground service operations at a hub airport - Parkan, Pinar; ozkir, Vildan (TAYLOR & FRANCIS LTD, 2020)
Airport terminals are dynamic environments and security/passport services generally constitute costly bottlenecks in terminals. Increases in the number of airline passengers compels airport terminals to provide more efficient services to its customers under space and resource limitations. This study examines the level of service of passenger processes at Istanbul Ataturk Airport by constructing a comprehensive simulation model. It focuses mainly on passport control services and passenger transfer security services because of the airport's hub status and the strategy of Turkish Airlines. The increasing number of transfer passengers may cause disruptions in departure flight schedules due to slow passenger processes. After validating the model, we investigate the consequences of three main alternative solutions, including 17 sub-scenarios, to capture target quality levels. Finally, we provide the results for each scenario to investigate the optimum allocation of resources to terminal operations.
Keywords: Airport ground services; simulation; security processes; scenario analysis; Istanbul Ataturk airport; FLOW; TIME; Transportation